An Educational Module For Pediatric Residents on Community, Home and School Violence - Mario Cruz; Sean Connolly; Daniel Taylor; Bruce Bernstein; Nancy Spector; Lee Pachter; Barry Solomon (Association of American Medical Colleges, 2013)
Abstract Introduction Many pediatric residents in urban settings work with patients who are chronically exposed to community violence. In fact, the major cause of death for male adolescents in most urban centers is homicide. This interactive, 90-minute, case-based module was designed so that pediatric residents would become more knowledgeable about the prevalence of community violence and the risk and protective factors for injury from community violence. In addition, the module aims to teach residents about effective strategies that can be used to reduce their patient's risk of future injury. Methods The module is designed for three participants: one general pediatrician (instructor) and two pediatric interns. This exercise should take place in a private and quiet office or conference room with enough seating for at least the three individuals. The room should have a computer with internet access available for the instructor to identify online resources for families. This module takes place as a required component of the intern advocacy block. It requires a total of 120-200 minutes to complete (90 minutes for the small-group case-based discussion and 30-110 minutes to prepare for the discussion by reading articles or watching a documentary). Results This curriculum improved resident knowledge and comfort in regard to a number of community violence-related issues. While the module was well received by our pediatric residents, it did not significantly change their self-reported behaviors. Discussion It is clear that a single, 90-minute module on such a challenging topic is not sufficient to meaningfully change the behaviors of pediatrics residents. Residents will likely need more hands-on experiences (such as directly observed clinical encounters, observed simulated clinical encounters, or role-plays) to more effectively change behavior.